1999
DOI: 10.1128/jcm.37.9.2904-2909.1999
|View full text |Cite
|
Sign up to set email alerts
|

International Multicenter Evaluation of the Clinical Utility of a Dipstick Assay for Detection of Leptospira -Specific Immunoglobulin M Antibodies in Human Serum Specimens

Abstract: We performed a multicenter evaluation of a robust and easily performed dipstick assay for the serodiagnosis of human leptospirosis. The assay is aimed at the detection of Leptospira-specific immunoglobulin M (IgM) antibodies. The study involved 2,665 serum samples collected from 2,057 patients with suspected leptospirosis in 12 countries on five continents with different levels of endemicity and different surveillance systems. The patients were grouped as laboratory-confirmed leptospirosis case patients and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 8 publications
0
12
0
4
Order By: Relevance
“…The results of the latex agglutination assay for the four study groups combined showed 89.4% agreement (kappa, 0.63; 95% confidence interval [CI], 0.57 to 0.69) with the results of the MAT, 95.2% agreement (kappa, 0.81; 95% CI, 0.75 to 0.87) with the results of the IgM ELISA, and 93.4% agreement (kappa, 0.74; 95% CI, 0.68 to 0.80) with the results of a dipstick assay for the detection of Leptospira-specific IgM antibodies, which we described previously (5,10,11,16). The sensitivity of the latex agglutination assay was somewhat lower than the sensitivity of the IgM ELISA, the specificity and positive predictive value were significant lower, and the negative predictive value was the same ( Table 2).…”
mentioning
confidence: 63%
“…The results of the latex agglutination assay for the four study groups combined showed 89.4% agreement (kappa, 0.63; 95% confidence interval [CI], 0.57 to 0.69) with the results of the MAT, 95.2% agreement (kappa, 0.81; 95% CI, 0.75 to 0.87) with the results of the IgM ELISA, and 93.4% agreement (kappa, 0.74; 95% CI, 0.68 to 0.80) with the results of a dipstick assay for the detection of Leptospira-specific IgM antibodies, which we described previously (5,10,11,16). The sensitivity of the latex agglutination assay was somewhat lower than the sensitivity of the IgM ELISA, the specificity and positive predictive value were significant lower, and the negative predictive value was the same ( Table 2).…”
mentioning
confidence: 63%
“…In these circumstances relatively simple assays such as the haemagglutination assay (Levett & Whittington 1998) may be used, but this assay has a limited sensitivity for samples collected early in the disease (Ef¯er et al 2000). Stability of assay reagents is an important prerequisite for tests used in tropical countries, and we recently described a dipstick assay (Gussenhoven et al 1997;Smits et al 1999;2000) and a latex agglutination test (Smit et al 2000b) for the detection of Leptospira-speci®c antibodies in human sera. The latex agglutination assay is performed by mixing on an agglutination card 5 ll serum with 5 ll antigen-coated, dyed latex beads.…”
Section: Introductionmentioning
confidence: 99%
“…Stability of assay reagents is an important prerequisite for tests used in tropical countries, and we recently described a dipstick assay ( Gussenhoven et al . 1997 ; Smits et al . 1999 , 2000) and a latex agglutination test ( Smits et al .…”
Section: Introductionmentioning
confidence: 99%
“…If the stage of the disease is unknown, both acute and immune phase tests are performed. Other serological test methods have previously been developed including flow cytometry [ 10 ], complement fixation testing [ 11 ], indirect hemagglutination assay [ 12 ] an IgM dipstick assay [ 13 ] and an IgM enzyme-linked immunosorbent assay (ELISA) in a number of formats [ 14 , 15 ]. Each of these assays has its advantages and disadvantages [ 16 ] and the type of assay used for diagnosis is generally dependant on the facilities available.…”
Section: Introductionmentioning
confidence: 99%